Estrategias empresariales corporativas que desarrollan los hoteles de tres estrellas de la ciudad de Trujillo. - Villalobos Romero, Viviana Nathaly (2018)
The thesis called CORPORATE BUSINESS STRATEGIES THAT DEVELOP THE HOTELS OF THREE STARS OF THE CITY OF TRUJILLO, was based on the variables called vertical integration type strategies and geographical positioning that hotels are currently developing to achieve the increase in demand tour; and whose data mentioned were extracted from primary information sources, such as the 31 administrators of the three-star hotels in the city of Trujillo (Centro Histórico and the surrounding area) that collaborated with the interview that was conducted; in addition to the 34 receptionists who, in order to maintain direct contact with the different areas of the hotel, were given an evaluation survey to corroborate data that the administrators mentioned; also in each hotel (34) an infrastructure and equipment card was completed to know the physical condition of the hotel spaces; and to the 79 clients (tourists and mostly corporate) who expressed whether the hotel develops business strategies and if they are satisfied with it. _x000D_ The sources of secondary information used were: the book "Estrategia Empresarial - Digital Marketing", by author Juan López García, produced in 2011, whose book makes an outstanding division of business strategies. It distinguishes them according to their development as corporate business strategies, social strategies and business strategies. _x000D_ The methods that were used were the Analytical-Synthetic one that allowed to approach the corporative business strategies developed in the hotels of three stars of the city of Trujillo, independently analyzing the strategies of vertical integration and those of geographic positioning, to later recompose the system and conclude on the way of development of these in hotels. The Ethnographic that allowed to relate to the tangible aspects of three-star hotels directly (staff, suppliers, distributors and customers) recording in detail what can be observed. _x000D_ The techniques that were used were the direct observation that allowed to gather features and tangible characteristics presented by three-star hotels regarding corporate business strategies; the signing technique which helped to synthesize the description of the corporate strategies of vertical integration and geographical positioning; the interview technique that was developed for the managers and / or administrators and the survey technique that was applied to the receptionists and clients to know the degree of satisfaction and comfort generated by the application of said strategies. _x000D_ Among the instruments used were: Specialized Technical Files for the collection of information on the strategies, which were presented with a Methodological Observation Guide to facilitate the work of gathering information. Field notebook which allowed us to capture the data that was observed in the field trips, being able to determine the favorable or unfavorable situation of the three-star hotels and the development of their strategies. In-depth interview questionnaire, to determine the form of development of the strategies, types, innovation and knowledge of these. Survey questionnaire which was used to identify personal data, satisfaction of the type of strategies, strategic alliances and suggestions for improvement. Digital Photographic Camera and Recorder to capture images and details in the study area, in order to complement the description of said strategies, as well as of all the own characteristics, which are necessary and indispensable for the practice of the tourist hotel activity.